Analisis Persepsi Orang Muda Jakarta mengenai Cancel Culture - Christopher Brian; Gabriella Santoso; Yasinta Astin Sokang (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Cancel culture has become an increasingly prominent phenomenon in the dynamics of social media. Although widely discussed, quantitative studies on how Indonesian youth perceive this issue remain limited. This study aims to describe how young people in Jakarta interpret cancel culture by examining the factors of gender, age, and duration of social media use. The research employed a descriptive quantitative approach through an online survey. The instrument was a questionnaire adapted from Autencio et al. (2020), covering three dimensions: the nature of cancel culture, personal experience, and its social impact. Data were collected from 85 respondents aged 17–39 years (α = 0.786). The results indicate significant variations in perception. Female respondents were more familiar with cancel culture and tended to be more cautious in expressing themselves, whereas male respondents were more consistent in supporting public figures despite controversies. Participants aged 22–39 years demonstrated reflective and critical understanding, while those aged 17–21 years were more reactive but less in-depth in evaluating social issues. The duration of social media use also influenced perceptions: low-intensity users showed critical attitudes, moderate users expressed balanced views, and high-intensity users were more familiar but prone to self-censorship. In conclusion, cancel culture is understood in diverse ways by young people in Jakarta, shaped by identity, digital experiences, and levels of critical literacy. Academically, this study contributes to enriching quantitative research on cancel culture in Indonesia. Practically, the findings highlight the importance of digital literacy programs to foster a healthy and inclusive digital environment.